Queering Christopher Kirkland (1885): Eliza Lynn Linton’s “Autobiography-in-Drag” - Nathalie SAUDO-WELBY (E-REA)
The life of the famous anti-feminist Eliza Lynn Linton (1822-1898) was full of contradictions, which are reflected in her fictionalized autobiography, The Autobiography of Christopher Kirkland (1885). As the first professional woman journalist in Britain, Linton castigated the emancipated woman. As a novelist, she drew damning caricatures of women rights supporters, while some of her rebellious women are depicted in a positive, albeit ambiguous, light. Although Christopher claims in the last pages that he “stand[s] absolutely alone”, the character has been constructed throughout the narrative mainly in inter-relational terms, and the story is peopled with positive, partly idealized, spiritual and intellectual godmothers and daughters. The sex reversals in the characters, some of whom may have been partly modelled upon Linton herself, allow her to construct herself as male, to exploit the Bildungsroman plot and to subvert traditionally gendered romance.My analysis will explore Linton’s piece of self-writing from the angle of feminist narratology. Linton’s radical adoption of a male persona creates situations in which the binary divisions s/he endorses as a journalist no longer hold true.